Development of an E-Module Based on the SAVI Learning Model on the Topic of Buffer Solutions - Cecilia Sijabat; Ramlan Silaban; Eddiyanto; Haqqi Nasution; Susilawati Amdayani; Irving Alexander; Dimas Ridho (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
The purpose of this research focuses on the development of electronic modules (e-modules) based on the SAVI (Somatic, Auditory, Visual, and Intellectual) learning model, which specifically targets high school students studying buffer solution materials. This research uses the 4-D model development framework, including the defining, designing, and developing stages. Initial needs analysis showed a significant gap in the utilization of electronic learning media at SMA Negeri 1 Pancur Batu. The resulting e-module consists of 39 pages and is designed to meet diverse learning styles through interactive elements and multimedia aids. Validation by experts showed that the e-module was very feasible, with an average value of 78.37% material expert assessment and 88.3% media expert assessment. In addition, feedback from teachers and students showed strong engagement and effectiveness, with an average teacher assessment score of 90.75% and 89% average student assessment. This research highlights the importance of integrating modern technological advances into chemistry education to improve student learning outcomes. Keywords: Development, E-module, Buffer solution, SAVI